Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Pada Cafe Candu Kopi - Tinaria, Lisa; Yulita, Rahma (Universitas Pahlawan Tuanku Tambusai, 2024)
Need of work may be a major issue. To overcome this, modern breakthroughs are required. Be that as it may, the challenge for society is need of instruction and aptitudes. As a arrangement, numerous select to open little businesses, such as coffee shops, which have awesome potential in case overseen legitimately. The reason of this inquire about and community benefit is to supply information and understanding into advanced showcasing methodologies in expanding deals at the Candu Kopi cafe. The strategies utilized are talk and hone strategies as well as mentoring for MSMEs. The time of usage is August 25, 2024 to September 26, 2024. The comes about of this think about are that this action requires tolerance, diligence, and advanced showcasing methodologies to present the commerce to potential clients with a more extensive reach, other than that advanced promoting procedures can increment deals at the Cafe Candu Kopi. Keywords: Candu kopi, Marketing Strategy, Digital